2014
DOI: 10.1099/mic.0.075580-0
|View full text |Cite
|
Sign up to set email alerts
|

A streptolysin S homologue is essential for β-haemolytic Streptococcus constellatus subsp. constellatus cytotoxicity

Abstract: Streptococcus constellatus is a member of the Anginosus group streptococci (AGS) and primarily inhabits the human oral cavity. S. constellatus is composed of three subspecies: S. constellatus subsp. constellatus (SCC), S. constellatus subsp. pharyngis and the newly described subspecies S. constellatus subsp. viborgensis. Although previous studies have established that SCC contains b-haemolytic strains, the factor(s) responsible for b-haemolysis in b-haemolytic SCC (b-SCC) has yet to be clarified. Recently, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…pharyngis SK1060 and S. constellatus subsp. viborgensis SK1359 (Tabata et al, ). In line with this published data, several independent observations support the hypothesis of SLS acquisition via horizontal gene transfer for S. anginosus .…”
Section: Discussionmentioning
confidence: 99%
“…pharyngis SK1060 and S. constellatus subsp. viborgensis SK1359 (Tabata et al, ). In line with this published data, several independent observations support the hypothesis of SLS acquisition via horizontal gene transfer for S. anginosus .…”
Section: Discussionmentioning
confidence: 99%
“…We have been investigating the pathogenic potential of β-hemolytic AGS, and had revealed that SLS is the sole hemolytic factor of the β-hemolytic AGS, except in S. intermedius that secretes the protein hemolysin intermedilysin [10,12]. In addition, we had revealed that the β-hemolytic S. constellatus subsp.…”
Section: Discussionmentioning
confidence: 99%
“…However, we had reported previously that the culture supernatant of the β-hemolytic S. constellatus subsp. constellatus strain W277 showed cytotoxicity to the human hepatocellular carcinoma cell culture line HepG2 [12]. Moreover, in our investigation on the SLS from β-hemolytic AGS strains, we had not ruled out the cytotoxic potential of the SLS secreted from these strains.…”
mentioning
confidence: 85%
See 2 more Smart Citations